Transforming commitment into performance: a study of digital transformation in the Cambodian public sector amidst a pandemic - Bora Ly (Cogent Business & Management, 2024)
This study examines the relationships between organizational commitment (affective, normative, and continuance), individual performance, and digital transformation within public sector organizations in Cambodia during the COVID-19 pandemic. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the research analyzes responses from 250 employees to investigate how different types of organizational commitment influence individual performance and the role of digital transformation in mediating these relationships. The findings reveal a statistically significant positive relationship between affective organizational commitment and individual performance, highlighting the importance of emotional attachment to the organization. Similarly, both normative and continuance commitments are found to impact individual performance and digital transformation efforts significantly. The study identifies digital transformation as a key mediator in the relationship between organizational commitment and individual performance, with varying degrees of mediation observed across different types of commitment. Specifically, digital transformation partially mediates the relationship between affective commitment and individual performance while exhibiting a full mediation effect in the relationship between normative commitment and individual performance. The study contributes to the existing literature by providing empirical evidence on the dynamics of organizational commitment, digital transformation, and individual performance in a unique context, offering insights for policymakers and organizational leaders on enhancing employee performance and driving successful digital transformation during crises. The research underscores the need for a nuanced understanding of employee commitment and engagement in facilitating digital transformation and improving performance outcomes in the public sector, particularly during challenging times.This study delves into how the dedication of employees to their organizations—encompassing emotional attachment, obligation, and perceived cost of leaving—affects their work performance within Cambodia's public sector during the COVID-19 pandemic, with a special focus on the role of digital upgrades in this dynamic. It finds that digital advancements play a crucial role in enhancing this performance, acting as a bridge between an employee's commitment to their organization and their job performance. Especially noteworthy is how these digital changes fully enhance the performance of those who stay out of a sense of duty. This research offers valuable insights into improving employee performance through digital technology, emphasizing its importance not just for business leaders and policymakers but for anyone interested in how workplaces can thrive during challenging times.
Keywords: 650; Organizational commitment; digital transformation; individual performance; public sector; covid-19